Enhancing adolescents’ exercise motivation management with generative AI anthropomorphism: a chain-mediated model of technology acceptance and self-efficacy - Wang, Kaiyuan; Li, Hongxin; Yu, Guo; Li, Gang; Song, Yu (Frontiers in Psychology, 2025)
IntroductionIn the era of human-machine integration, digital technology highlights its important enabling role in the development of youth sports. The objective of this study is to examine the mechanism through which AI Anthropomorphism is associated with exercise motivation among adolescents.MethodsThe data were derived from a sample of 1,018 adolescents aged 6–18 across the country. The AI anthropomorphism scale, the Generative artificial intelligence acceptance (GAIA), the General Self-Efficacy Scale (GSES), and the Physical Activity Motivation Scale (MPAM-R) were used to assess AI anthropomorphism, technology acceptance, self-efficacy and exercise motivation.ResultsThis study found that AI anthropomorphism is significantly associated with adolescents’ motivation for physical activity. Further analysis reveals that technology acceptance and self-efficacy independently serve as mediators and chain mediators, respectively, in this relationship, clarifying the underlying psychological mechanisms.ConclusionThis study elucidates the mechanism by which AI anthropomorphism is associated with adolescents’ motivation for exercise motivation, offering theoretical support for understanding such behavior and practical guidance for implementation.